What is The simplified form of (3a2 - 5ab plus c2) plus (-2a2 plus 10ab plus 6c2)
2x+2 The commonality is 2, so you write 2(x+1) and it is factored.
9x2+2x-7 = (9x-7)(x+1) when factored
2(a+b) is 2a plus 2b in factored form.
It is (x+4)(x+5) when factored
w2+18w+77 = (w+7)(w+11) when factored
18 + 8x + x = = 18 + 9x = 9(2 + x) which is the factored form of the expression.
2x + 3 can be factored as follows: 2(x + 1.5)
5a(2b + 1)
6x2+5x+1 = (3x+1)(2x+1) when factored
It can't be factored because its discriminant is less than zero
10(u + 30)
2x(3x + 5)
It's the general form of a quadratic expression and it can be factored providing its discriminant is not less than zero.
(x + 5)2
Dividing all terms by 2 gives: 6x2+7x+2 = (2x+1)(3x+2) when factored
Yes, it can. ANY equation of this form can be factored. The factors may not be integers or even real numbers, though.
5x + 70 = 5 (x + 14)
2p + 34 = 2*(p + 17)
25m + 22p is in its simplest form.